Effect of coupling in ductile/brittle plastic laminate subjected to tensile load - Lua, Wei Chek (Nanyang Technological University, 2024)
This project investigates the coupling effects in ductile/brittle laminates under bending loads. Acrylic is used to simulate brittle metal while polycarbonate is used to simulate ductile metal characteristics. The materials are laminated in various combinations to create four different setups, each with a total thickness of 8 mm. Epoxy adhesive is used to bond the specimens together. Experimental tests are conducted, subjecting the specimens to loads ranging from 50 g to 500 g. The experimental results are then compared with theoretically calculated values of Young's modulus. It is observed that the experimental values closely align with the theoretical predictions, indicating the linearity of the results. The findings also reveal a coupling effect between the acrylic and polycarbonate laminate, consistent with our study's objective to explore the interaction between brittle and ductile metals. It is found that the bending deflection increases with added weight.